Understanding pedagogical content knowledge from Islamic epistemology among Muslim educators in Tanzania - Janja, Mnyero (2016)
In line with teacher education reform, it is essential to understand pedagogical content knowledge (PCK) from epistemological views among educators. This research inquiry aimed to unveil meaning, nature and approaches that Muslim educators engage in understanding of PCK. The study focused on PCK as interpreted, experienced, processed and understood from Muslim educators’ perspectives and in what ways those views fit Islamic epistemology of knowledge, education and learning. This qualitative phenomenological research inquiry purposively sampled eight Muslim educators with rich teaching and education related working experiences. With hermeneutic phenomenology, the respondents were engaged to reflect their experiences that matter most on the aspect of PCK through probing questions. Data were collected through in-depth semi-structured interviews and were transcribed verbatim before being analysed through Interpretative Phenomenological Analysis Approach. Analytically, the researcher used this approach to focus on the rich parts of the interviews and get initial themes from the transcript of each respondent as an individual case. Thereafter, conceptual connections were made within and across themes to transform initial themes into abstraction before they were connected together in more meaningful themes. Emerged themes were cross-checked with the individual transcripts to note additional information and deepen analysis. Finally, the researcher used the theme of the first case to identify other themes with similar meanings and ended up by developing a master list of more concise themes. The findings revealed that Tawhidic thinking underpinned unified meaning of PCK among Muslim educators. That meaning ranged from foundational to predominant or self-authorship level. At foundational level, knowledge of learner and self, and knowledge of subject matter were just conceptualised as generic and simplistic ones. At transitional level, shifting integrated knowledge of curriculum and context was shown while at predominant level, self-authorship or predominant Islamic pedagogy became fully realised. Equally, it was revealed that basic understanding of Divine revelation featured integration of reasoning and empirical observation with revealed knowledge in hierarchical order to define the nature of PCK. In addition, it was unveiled that embedded Tawhidic thinking in the form of recognition of Allah and observing sincerity of intention and learning culture underpinned memorisation with understanding, articulation and intenalisation of values, manifestation or implementation as holistic integrated learning processes of PCK. Upon intensely tied all themes on the meaning, nature and learning approach with ingrained Tawhidic thinking, therefore, Tawhidic pedagogical content knowledge emerged. It can be concluded that Tawhidic thinking is the key to conceptualisation of unified meaning of PCK needed for educating good human consistent to their grand purpose and mission of life. Moreover, informed Muslim educators seek to establish strong physical-metaphysical unification of knowledge that focus to educate quality teachers who can face professional and global challenges to succeed in this world and Hereafter. Furthermore, it is primarily vital to appreciate the essence of ingrained Tawhidic thinking to better understand how Muslim educators’ beliefs shape their experiences on learning approach and understanding of PCK. The findings of this research have implications that effective meaning of PCK is consistent to wholeness of learner and of self. In addition, effective Muslim educators are committed to holistic- integrated nature of knowledge for significant learners’ lasting achievements. The spirit on learning and understanding of PCK amongst Muslim educators is to transform and educate complete being, regardless challenges.